An NIR‐II‐Emissive Photosensitizer for Hypoxia‐Tolerant Photodynamic Theranostics. Issue 45 (7th October 2020) - Li, Lanqing; Shao, Chen; Liu, Tao; Chao, Zhicong; Chen, Huanle; Xiao, Fan; He, Huamei; Wei, Zixiang; Zhu, Yulin; Wang, Huan; Zhang, Xindan; Wen, Yating; et al.
Abstract: As a common feature in a majority of malignant tumors, hypoxia has become the Achilles' heel of photodynamic therapy (PDT). The development of type‐I photosensitizers that show hypoxia‐tolerant PDT efficiency provides a straightforward way to address this issue. However, type‐I PDT materials have rarely been discovered. Herein, a π‐conjugated molecule with A–D–A configuration, COi6‐4Cl, is reported. The H2 O‐dispersible nanoparticle of COi6‐4Cl can be activated by an 880 nm laser, and displays hypoxia‐tolerant type I/II combined PDT capability, and more notably, a high NIR‐II fluorescence with a quantum yield over 5%. Moreover, COi6‐4Cl shows a negligible photothermal conversion effect. The non‐radiative decay of COi6‐4Cl is suppressed in the dispersed and aggregated state due to the restricted molecular vibrations and distinct intermolecular steric hindrance induced by its four bulky side chains. These features make COi6‐4Cl a distinguished single‐NIR‐wavelength‐activated phototheranostic material, which performs well in NIR‐II fluorescence‐guided PDT treatment and shows an enhanced in vivo anti‐tumor efficiency over the clinically approved Chlorin e6, by the equal stresses on hypoxia‐tolerant anti‐tumor therapy and deep‐penetration imaging. Therefore, the great potential of COi6‐4Cl in precise PDT cancer therapy against hypoxia challenges is demonstrated. Abstract : An A–D–A‐type π‐conjugated molecule, COi6‐4Cl, is synthesized and exploited in tumor theranostics. COi6‐4Cl absorbs 880 nm light to emit bright NIR‐II emission and exert type‐I/II combined photodynamic reactions, which can realize deep‐penetration fluorescence imaging and hypoxia‐tolerant photodynamic therapy simultaneously by the same NIR‐light irradiation. These features make COi6‐4Cl a distinguished single‐NIR‐wavelength‐activated phototheranostic material.